الدور الاقتصادي والاجتماعي لقطاع السياحة في سورية (دراسة تحليلية لمؤشرات الاقتصاد السياحي للفترة 2003-2008) - محمود حبيب; شوباصي شعبان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
أصبح قطاع السياحة أحد أهم دعائم الاقتصاد الوطني في سورية، وهو المحور الأساسي لقطاع الخدمات، وقد بلغت مساهمة اقتصاد السياحة والسفر (11.2%) من الناتج المحلي الإجمالي لسورية لعام 2008 بما يعادل مبلغ /5.13/ مليار دولار، حيث وصل عدد السياح الذين زاروا سورية إلى /5.43/ مليون سائح لنفس العام وقد أنفقوا /199.4/ مليار ليرة سورية بزيادة /92%/ عن عام 2005 (بحسب منظمة السياحة العالمية WTO)، وهذا التطور في القطاع السياحي انعكس في العديد من الجوانب الاقتصادية والاجتماعية مثل زيادة الإيرادات العامة للدولة، وتشغيل مئات الألوف من العمال.. بناءً على ما تقدم جاء هذا البحث حتى يسلّط الضوء على الدور الاقتصادي والاجتماعي لقطاع السياحة في سورية من المنظور الكلي للفترة (2003-2008)، متناولاً بالترتيب أهم الأفكار التي تخدم الموضوع وفقاً للمحاور التالية: - الفرق بين الاقتصاد السياحي وصناعة السياحة، وكيفية زيادة مساهمتهما في الناتج المحلي الإجمالي (GDP). - الصادرات السياحية ودور الإيرادات السياحية في تصحيح ميزان المدفوعات. - العمالة السياحية المباشرة وغير المباشرة، وكيفية زيادتها كمّاً ونوعاً. - النتائج والتوصيات. Tourism sector has become one of the most important pilings of national economy in Syria, and it is the basic axis of services sector. The contribution of the economy of tourism and travel reached (11.2%) of the GDP in 2008 which equals (5.13) billion dollar. The tourists number who visited Syria reached (5.43) million tourists in 2008, and they spent (199.4) billion SP with increasing (92%) than in 2005 (according WTO). This developing in tourism sector is reflected in many economic and social sides, such as increasing the governmental receipts and employing hundreds of thousands of workers. Depending on the above-mentioned points, this paper has studied the economic and social role of the Syrian tourism sector on macroeconomic level between (2003-2008), by searching in the following issues that serve the goals of the subject: - The difference in concept between tourism economy and tourism industry, and how to increase their contribution in GDP. - The Tourism exports and the role of tourism receipts in correcting the balance paid. - The Tourism employment direct and indirect, and how to increase them in quality and quantity. - Results and recommendations.